Pengembangan Video Pembelajaran Fisika Berbasis STEM untuk Meningkatkan Minat dan Hasil Belajar Siswa - Devi, Berliana Sintia; Subali, Bambang (UPEJ Unnes Physics Education Journal, 2021)
The aim of this research is to analyze the influence of STEM–based physics learning video (Science, Technology, Engineering, and Mathematics) towards the improvement of interest and student learning results. The method used was research and development (R&D. The research design used in implementation of STEM based physics learning video was Pretest-Posttest Control Group Design with control class research subject was XI MIPA 1 and research subject of experimental class was XI MIPA 3. The implementation of STEM based physics learning video in learning can improve student interest in learning. This is indicated by results of t-test obtained by Sig. (2-tailed), namely 0.000 < 0.05 and N-gain test showing that there was an increase in student interest in learning by 0.51 in